Participation Is Everything: Evangelism from the point of view of a Brazilian Pentecostal - Mello, Manoel de (International review of mission, 1971)
This document is taken from an interview granted to the editor of O Expositor Cristao by Pastor Manoel de Mello. We have omitted the questions and consolidated the answers. Manoel de Mello is a leader of the Brazilian Igreja Evangélica Pentecostal “Brasil para Cristo” — a Pentecostal denomination with about one million members. In São Paulo, Manoel de Mello is building the largest church in the world. It seats 25,000 people, and has many additional halls and rooms for adult education, workshops, etc. De Mello was one of the Pentecostals from Latin America who attended the Fourth Assembly of the World Council of Churches at Uppsala. He also was guest of the Assembly of the Lutheran World Federation at Evian (1970), where — in fact — he was, for part of the time, the only representative of a Brazilian Church. In the report below he states the reasons why his church has decided to join the WCC. The editors of the news-service of the Centro Evangélico de Informação (São Paulo) introduce the report with the following noteworthy remark: “With this ecumenical consciousness directed towards renewal, the Pentecostals should become the greatest revolutionary force in Protestant thought in Brazil.” Editor